1981
DOI: 10.1002/anie.198109871
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Water by Visible‐Light Irradiation of Colloidal CdS Solutions; Inhibition of Photocorrosion by RuO2

Abstract: The conversion of light into chemical fuels in photochemical devices equipped with semiconductor electrodes (e.g. of n‐CdS) is associated with a serious problem: “holes” produced in the valence band of the semidonductor upon irradiation migrate to the surface where photocorrosion occurs. In mi‐croheterogenous CdS systems this is remedied by a thin layer of RuO2. A CdS sol prepared in the presence of maleic anhydride/styrene copolymer has now been loaded with RuO2 and Pt; these CdS microelectrodes are surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 24 publications
1
99
0
1
Order By: Relevance
“…The final pH was adjusted as required for subsequent experiments. The absorption spectra of the sols made in this fashion matched those reported by others [6,7].…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…The final pH was adjusted as required for subsequent experiments. The absorption spectra of the sols made in this fashion matched those reported by others [6,7].…”
Section: Methodssupporting
confidence: 83%
“…In the presence of O2 the following mechanism may be proposed to explain the photodegradation of a metal sulphide (MS) (5) (6) (7) (8) (9) …”
Section: Discussionmentioning
confidence: 99%
“…The enolate ligand nucleophilically attacks a second acetone molecule to form a C À C bond (12), and the aldolate ligand is coordinated to the Ti center (13). This titanium diacetone alcoholate complex can either react to give a TiÀOH species under release of mesityl oxide and further proceed to the formation of a Ti-O-Ti bond (14), or undergo further condensation reaction with a third acetone molecule. [209] In the latter process, complex 15 is transformed into the tridentate ligand 16, which is an excellent stabilizing agent.…”
Section: Nonaqueous Sol-gel Chemistry For Metal Oxide Synthesismentioning
confidence: 99%
“…All electronic properties in semiconducting crystallites. [8][9][10][11][12] Intensive work on semiconductor-doped glasses [13] and on the photocatalytic properties of colloidal CdS [14,15] finally resulted in the description of the quantum-size effect more than 20 years ago. Brus et al found that CdS crystallites in the size range of a few nanometers did not have the electronic spectra of the bulk material, even though they exhibited the same unit cell and bond length as the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…Among these photocatalysts, hexagonal CdS as one of the most important II-VI group semiconductors has received much more attention in utilizing solar energy due to its band gap (2.4 eV) matching well with the solar spectrum [12][13][14][15][16]. For improving the photocatalytic activity of CdS, the processes in the photocatalytic reaction, including the generation, separation, recombination and migration of the photogenerated electrons and holes, should be comprehensively investigated [17,18].…”
Section: Introductionmentioning
confidence: 99%